International auditing standards - Stamp, Edward; Moonitz, Maurice (Englewood Cliffs, N.J. : Prentice-Hall International, 1978)
Analyzes and describes the nature of auditing the need for international auditing standards, and the current auditing situation in nine major countries.
Includes bibliographical references: p. 153-159.
kjo 15/01/2019
Loans
Keywords: Auditing